Elampus bidens - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
2. Elampus bidens (Förster, 1853) Notozus bidens Förster 1853: 335. Holotype ♀; Poland: Silesia (ZMB) (examined). Remarks. The species has been reported from Denmark by Allearter.dk (2010). According to K. Runge Poulsen ( in litt. ) the record was based on one specimen, collected from NEZ : Tibirke Bakker 15.VII.1913 (coll. Klöcker) and deposited in ZMUC. We have checked this specimen, which belongs to the species E. panzeri . Thus E. bidens should be removed from the Danish fauna. : Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on page 51, DOI: 10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433 : {"references": ["Forster, A. (1853) Eine Centurie neuer Hymenopteren. Beschreibungen neuer Arten aus der Familae der Chrysididen. Verhanlungen des naturhistorischen Vereins der preussischen Rheinlande und Westfalens, 10, 266 - 362."]}